2024
DOI: 10.1111/psrh.12254
|View full text |Cite
|
Sign up to set email alerts
|

Exploring provider preference and provision of abortion methods and stigma: Secondary analysis of a United Kingdom provider survey

Katy Footman,
Suzanna Bright,
Jayne Kavanagh
et al.

Abstract: IntroductionMethod choice is an important component of quality abortion care and qualitative research suggests that abortion stigma can influence provider preference and provision of abortion methods. This study is the first to explore the relationships between abortion providers' method preferences, their provision of medication or instrumentation abortion or both methods, and abortion stigma.MethodsWe conducted secondary analysis of a survey of United Kingdom (UK) abortion providers (N = 172) to describe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous studies have found that both practitioners and clients were more likely to provide/choose a medical method where medical abortion at home is legally permitted. [12][13][14] During the COVID-19 pandemic, the 'contactless' provision of the mifepristone-misoprostol medication abortion care strategy was extensively validated as safe and effective and was popular. 15 However, the preferences for provision/choice of abortion methods in China are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that both practitioners and clients were more likely to provide/choose a medical method where medical abortion at home is legally permitted. [12][13][14] During the COVID-19 pandemic, the 'contactless' provision of the mifepristone-misoprostol medication abortion care strategy was extensively validated as safe and effective and was popular. 15 However, the preferences for provision/choice of abortion methods in China are still unknown.…”
Section: Introductionmentioning
confidence: 99%